Molecular Farming Strategy for the Rapid Production of Protein-Based Reagents for Use in Infectious Disease Diagnostics - Shanmugaraj, Balamurugan; Jirarojwattana, Perawat; Phoolcharoen, Waranyoo (Planta Medica, 2023)
Recombinant proteins are a major breakthrough in biomedical research with a wide range of applications from diagnostics to therapeutics. Strategic construct design, consistent expression platforms, and suitable upstream and downstream techniques are key considerations to produce commercially viable recombinant proteins. The recombinant antigenic protein production for use either as a diagnostic reagent or subunit vaccine formulation is usually carried out in prokaryotic or eukaryotic expression platforms. Microbial and mammalian systems dominate the biopharmaceutical industry for such applications. However, there is no universal expression system that can meet all the requirements for different types of proteins. The adoptability of any expression system is likely based on the quality and quantity of the proteins that can be produced from it. The huge demand of recombinant proteins for different applications requires an inexpensive production platform for rapid development. The molecular farming scientific community has been promoting the plant system for nearly 3 decades as a cost-effective alternative to produce high-quality proteins for research, diagnostic, and therapeutic applications. Here, we discuss how plant biotechnology could offer solutions for the rapid and scalable production of protein antigens as low-cost diagnostic reagents for use in functional assays.
Keywords: Biopharmaceuticals; diagnostics; molecular farming; plant biotechnology; recombinant proteins; transient expression